ICT’s and the government of (in) security in argentina: Progress of an exploratory study (Delito y Sociedad, 2019)
In this article, we present the advances of an exploratory research on the use of new information and communication technologies in the field of (in) security government. This initial exploration addresses the way in which the terms ICTs-security-insecurity are linked, taking as reference two fields of practice. On the one hand, that of normative production. What kind of rules regulate the uses of ICTs associated with the government of (in) security? How does this normative production relate to the way in which the field of government of (in) security is organized or structured?On the other hand, we approach the field of public debates. In this first stage of work we explored the way in which the use of video surveillance technologies is problematized in the graphic media. How are video surveillance socially justified? What frames of senses associate security and video surveillance?This work explains the main theoretical coordinates of our analysis, describes the methodology used and presents the main advances obtained respecting these questions. Finally, there are some projections and lines of work that we intend to follow to the future.
Keywords: ICT; (In) Security; Control; Video surveillance; SIBIOS